Tracing Haavelmo's steps from confluence analysis to the probability approach - Olav Bjerkholt (University of Oslo, Department of Economics, 2001)
This article narrates Trygve Haavelmo's experiences from the time he was hired as an assistant at Ragnar Frisch's Institute of Economics in 1933 until the publication of The Probability Approach in Economics in 1944. The title should be taken literally, it is Haavelmo's physical steps which are recounted rather than his thought processes. His meetings with others who contributed to the foundation of modern econometrics are mentioned, but with no attempt at making this a contribution to the history of econometrics. Particular attention is given to the communication between Frisch and Haavelmo in this period, also their sometimes half joking exchanges.
Keywords: 330; Norwegen